Effect of organic amendments on yield of Pleurotus spp. in Arunachal Pradesh - Singh, Satya Pal; Bhagawati, R; Chandra, Anup (Mushroom Research, 2012)
Seven different nitrogenous supplements along with control were tried with paddy straw for the cultivation ofÂ  P. flabellatus and P. florida. Each bag of 30 x 20 cm size (125 gauge) weighed approximately five kg Â (equivalent to 1.5 kg dry paddy straw). Before filling, the moist basal substrate was mixed separately with five per cent of individual supplement (pre-treated with a chemical solution of 125 ml formalin and 5 g bavistin) in 15 kg of substrates. P. florida and P. flabelattus spawn were prepared on paddy grains. In respect of P. flabellatus, the maximum sporophore yield of 1350g was observed with substrate supplemented with wheat bran, which was followed closely by rice bran (1140g). The data also showed a respective increase of 92.84 and 62.84 per cent yield over the control (700 g). All other treatments were superior to control except one, yielding as low as 600 g with neem cake powder. In P. florida, paddy straw supplemented with rice bran elicited a maximum yield of 1360 g followed by 1225 g 1210 g, 1100 g, 1085g, 1075 g, and 660 g with wheat bran, mustard seed cake powder, black gram powder, chicken manure, maize powder, and neem cake powder respectively, showed an respective increase in yield to the extent of 70.00, 53.14, 51.26, 37.50, 35.62, 34.38 but 17.49 % decrease over the control. Â